Feasibility Analysis of Curcuma’s Effervescent Industry - Sukardi, Sukardi; Puteri, Saptariyanti A.K.; Taryana, Asep (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
There are more than 2,200 of 20,000 world’s total deposit of medical herbs found in Indonesia. Between 1994 and 1999, the medicinal herbs export value and volume increased 24.33% and 65.33% respectively. The value of world medical herbs trade increased around 25 billion dollars between 2000 and 2001. One of the potential herbs to be developed is Temulawak (Curcuma xanthorrhiza Roxb) which is useful to keep the health of lever (hepatoprotector) and also cure other symptoms. This research is aimed to determine the feasibility of establishing the effervescent tablet industry made from temulawak extract. According to market and marketing analyses, the average market value for this product nationally is around Rp 17.84 billion. With production capacity of 1,368,000 tubes/year this product will gain approximately 15% of market value, which is around Rp 2.68 billion. Each tube consists of 10 tablets at the price of Rp 19,572. Toll manufacturing system was chosen to increase efficiency and reduced the risk from marketing failure. This industry investment opportunity is required approximately Rp 10.5 billion investment. The analysis shows that with the equity between internal fund and bank loan of 50:50 resulted in internal rate of return of 35.66% which is higher than the predetermined minimum attractive rate of return of 20%, the net present value of Rp 14.47 billion, and the payback period of 4.41 year at the 10 year project cycle. Sensitivity analysis includes variabel cost and projected revenue. Based on the entire project analysis, this industry is considered feasible to conduct.Keywords: temulawak, effervescent, analysis, feasibility